2015
DOI: 10.5511/plantbiotechnology.15.0521a
|View full text |Cite
|
Sign up to set email alerts
|

<i>Peanut stunt virus</i>-induced gene silencing in white lupin (<i>Lupinus albus</i>)

Abstract: White lupin (Lupinus albus L.) plants develop cluster roots and have strong resistance to phosphorus starvation. Although many expressed sequences have been identified to explain the mechanisms used by white lupin to acquire phosphorus, the lack of a stable transformation technique has made it challenging to evaluate the functions of these expressed sequences. Virus-induced gene silencing (VIGS) is an attractive method for assaying gene function in species that are difficult to stably transform. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…While transformation efficiencies are low due to low survival and chimeric nature of T 0 plants, this method has been successful in generating transgenic NLL ( Molvig et al, 1997 ; Pigeaire et al, 1997 ; Wijayanto et al, 2009 ; Tabe et al, 2010 ; Atkins et al, 2011 ; Barker et al, 2016 ), L. luteus ( Li et al, 2000 ; Pniewski et al, 2006 ), and L. mutabilis ( Babaoglu et al, 2000 ; Polowick et al, 2014 ) to confer various traits, with recent modifications improving this transformation method for NLL ( Nguyen et al, 2016a , b ). For L. albus , however, A. tumefaciens -mediated transformation has been unsuccessful and as such hairy root transformation using A. rhizogenes ( Uhde-Stone et al, 2005 ; Sbabou et al, 2010 ; Cheng et al, 2011 ) and VIGS using the Peanut stunt virus vector ( Yamagishi et al, 2015 ) have been used to study gene function in this species. Metabolite profiling is an additional resource that could be enhanced in lupins to provide a valuable understanding of how the QA pathway interacts with other metabolic pathways in the plant, especially under abiotic and biotic stresses.…”
Section: Future Prospectsmentioning
confidence: 99%
“…While transformation efficiencies are low due to low survival and chimeric nature of T 0 plants, this method has been successful in generating transgenic NLL ( Molvig et al, 1997 ; Pigeaire et al, 1997 ; Wijayanto et al, 2009 ; Tabe et al, 2010 ; Atkins et al, 2011 ; Barker et al, 2016 ), L. luteus ( Li et al, 2000 ; Pniewski et al, 2006 ), and L. mutabilis ( Babaoglu et al, 2000 ; Polowick et al, 2014 ) to confer various traits, with recent modifications improving this transformation method for NLL ( Nguyen et al, 2016a , b ). For L. albus , however, A. tumefaciens -mediated transformation has been unsuccessful and as such hairy root transformation using A. rhizogenes ( Uhde-Stone et al, 2005 ; Sbabou et al, 2010 ; Cheng et al, 2011 ) and VIGS using the Peanut stunt virus vector ( Yamagishi et al, 2015 ) have been used to study gene function in this species. Metabolite profiling is an additional resource that could be enhanced in lupins to provide a valuable understanding of how the QA pathway interacts with other metabolic pathways in the plant, especially under abiotic and biotic stresses.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Using Potato virus X as a silencing vector in dicotyledonous species, inserts were lost with each subsequent passage to an uninfected Nicotiana benthamiana plant (Avesani et al, 2007). A Peanut stunt virus vector also displayed greater instability for maintaining larger PDS inserts (Yamagishi et al, 2015). Recently, Mei et al (2016) demonstrated a good correlation between the loss of a PDS fragment insert in a Foxtail mosaic virus silencing vector and the loss of post-transcriptional silencing.…”
mentioning
confidence: 99%
“…In viral vector systems, constraints on the size of insert fragments have often been reported, where larger inserts are more susceptible to being lost from the vectors (Hsieh et al 2013;Senthil-Kumar and Mysore 2011a;Yamagishi et al 2015). In the present study, deletion of the 33-nt LlPDS fragment in the CMV-HL from the P33-1 plant was not detected in the first year, but was detected in the following year.…”
Section: Discussionmentioning
confidence: 56%
“…Short interfering RNAs (siRNAs) were transcribed into cDNA using the stemloop pulsed RT protocol, and then, end-point PCR was conducted to amplify 60-nt fragments that included the siRNA sequences (Varkonyi-Gasic et al 2007;Yamagishi et al 2015) using primers shown in Supplementary Table S2. The primers were designed based on siRNA sequences that were predicted using the algorithm of Ui-Tei et al (2004) and Reynolds et al (2004); e.g., A or U at the 5′ terminal end of the guide strand, G or C at the 5′ terminal end of the passenger strand, and base preferences at positions 3 (A), 10 (U), and 13 (A, U, or C) of the passenger strand.…”
Section: Detection Of Sirna By Stem-loop Pulsed Rt and End-point Pcrmentioning
confidence: 99%